Business development while transforming the economy on the example of the city of Perm - E. V. Rozhkov (Вестник университета, 2021)
The purpose of the study is to identify the essence of digitalization for business. The theoretical and methodological relevance of the article consists in the fact that the issue of publicity of digitalization processes for small and medium-sized businesses have not until now considered by economists. The lack of development of these issues predetermined the relevance and practical significance of the study. The scenario of digitalization implementation has been considered on the example of Perm, where digitalization is carried out in accordance with the approved “Concept of digital economy development in the Perm Region”. The task of determining the economic effect of business processes digitalization in the city economy was solved. The following methods were used in the study: methods of statistical information processing, the general scientific method of cognition of the problem, the method of system analysis, the theory of digitalization of systems, computational and experimental methods for modeling the digitalization of property, as well as methods based on the theory of functional specialization and the theory of restructuring. It has been concluded that the introduction of digital technologies into public life allows businesses to take part in this and develop themselves.